Answer:
6 minutes
Step-by-step explanation:
'a' in the formula represents altitude in feet. You are told the altitude is 21000 feet, so put that into the formula:
21000 = 3400t +600
You can solve this for t:
20400 = 3400t . . . . . subtract 600 from both sides
6 = t . . . . . . . . . . . . . . . divide both sides by 3400
The problem statement tells you that t represents minutes after lift off, so this solution means the altitude is 21000 feet 6 minutes after lift off.
The question is asking for the number of minutes after lift off that the plane reaches an altitude of 21000 feet, so this answers the question directly:
The plane is at an altitude of 21000 feet 6 minutes after lift off.
Let r be a radius of a given circle and α be an angle, that corresponds to a sector.
The circle area is
![A=\pi r^2](https://tex.z-dn.net/?f=A%3D%5Cpi%20r%5E2)
and denote the sector area as
![A_1](https://tex.z-dn.net/?f=A_1)
.
Then
![\dfrac{A_1}{A}= \dfrac{\alpha}{2\pi}](https://tex.z-dn.net/?f=%20%5Cdfrac%7BA_1%7D%7BA%7D%3D%20%5Cdfrac%7B%5Calpha%7D%7B2%5Cpi%7D%20)
(the ratio between area is the same as the ratio between coresponding angles).
![A_1=\dfrac{\alpha}{2\pi} \cdot A=\dfrac{\alpha}{2\pi} \cdot \pi r^2= \dfrac{r^2\alpha}{2}](https://tex.z-dn.net/?f=A_1%3D%5Cdfrac%7B%5Calpha%7D%7B2%5Cpi%7D%20%5Ccdot%20A%3D%5Cdfrac%7B%5Calpha%7D%7B2%5Cpi%7D%20%5Ccdot%20%5Cpi%20r%5E2%3D%20%5Cdfrac%7Br%5E2%5Calpha%7D%7B2%7D%20)
.
The answer is 12 1/4. how I got my answer.
Their are 4 quarters to a whole, so that means all I have to do is multiply 4×3=12, then add 1/4+12= 12 1/4.
I hope this helps!
Function transformation involves changing the form of a function
The function g(x) is ![\mathbf{g(x) = 8(2)^x}](https://tex.z-dn.net/?f=%5Cmathbf%7Bg%28x%29%20%3D%208%282%29%5Ex%7D)
The function is given as:
![\mathbf{f(x) = 3^x}](https://tex.z-dn.net/?f=%5Cmathbf%7Bf%28x%29%20%3D%203%5Ex%7D)
g(x) is an exponential function that passes through points (-2,2) and (-1,4).
An exponential function is represented as:
![\mathbf{y = ab^x}](https://tex.z-dn.net/?f=%5Cmathbf%7By%20%3D%20ab%5Ex%7D)
At point (-2,2), we have:
![\mathbf{2 = ab^{-2}}](https://tex.z-dn.net/?f=%5Cmathbf%7B2%20%3D%20ab%5E%7B-2%7D%7D)
At point (-1,4), we have:
![\mathbf{4 = ab^{-1}}](https://tex.z-dn.net/?f=%5Cmathbf%7B4%20%3D%20ab%5E%7B-1%7D%7D)
Divide both equations
![\mathbf{\frac 42=\frac{ab^{-1}}{ab^{-2}}}](https://tex.z-dn.net/?f=%5Cmathbf%7B%5Cfrac%2042%3D%5Cfrac%7Bab%5E%7B-1%7D%7D%7Bab%5E%7B-2%7D%7D%7D)
Simplify
![\mathbf{2=\frac{b^{-1}}{b^{-2}}}](https://tex.z-dn.net/?f=%5Cmathbf%7B2%3D%5Cfrac%7Bb%5E%7B-1%7D%7D%7Bb%5E%7B-2%7D%7D%7D)
Apply law of indices
![\mathbf{2=b^{-1+2}}](https://tex.z-dn.net/?f=%5Cmathbf%7B2%3Db%5E%7B-1%2B2%7D%7D)
![\mathbf{2=b}](https://tex.z-dn.net/?f=%5Cmathbf%7B2%3Db%7D)
Rewrite as:
![\mathbf{b =2}](https://tex.z-dn.net/?f=%5Cmathbf%7Bb%20%3D2%7D)
Substitute 2 for b in ![\mathbf{2 = ab^{-2}}](https://tex.z-dn.net/?f=%5Cmathbf%7B2%20%3D%20ab%5E%7B-2%7D%7D)
![\mathbf{2 =a(2^{-2})}](https://tex.z-dn.net/?f=%5Cmathbf%7B2%20%3Da%282%5E%7B-2%7D%29%7D)
This gives
![\mathbf{2 =a(\frac 14)}](https://tex.z-dn.net/?f=%5Cmathbf%7B2%20%3Da%28%5Cfrac%2014%29%7D)
Multiply both sides by 4
![\mathbf{a = 8}](https://tex.z-dn.net/?f=%5Cmathbf%7Ba%20%3D%208%7D)
Substitute 8 for (a) and 2 for (b) in ![\mathbf{y = ab^x}](https://tex.z-dn.net/?f=%5Cmathbf%7By%20%3D%20ab%5Ex%7D)
![\mathbf{y = 8(2)^x}](https://tex.z-dn.net/?f=%5Cmathbf%7By%20%3D%208%282%29%5Ex%7D)
Express as a function
![\mathbf{g(x) = 8(2)^x}](https://tex.z-dn.net/?f=%5Cmathbf%7Bg%28x%29%20%3D%208%282%29%5Ex%7D)
Hence, the function g(x) is ![\mathbf{g(x) = 8(2)^x}](https://tex.z-dn.net/?f=%5Cmathbf%7Bg%28x%29%20%3D%208%282%29%5Ex%7D)
Read more about exponential functions at:
brainly.com/question/11487261